1995
DOI: 10.1111/j.1365-2249.1995.tb03475.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma (IFN-γ) production by human T lymphocytes uponLegionella pneumophilastimulationin vitro

Abstract: SUMMARYIn vitro immune responses to Legionella pneumophila were investigated. When human peripheral blood lymphocytes (PBL) from healthy volunteers were stimulated with formalin-kilied L. pneumophila for 7 days in vitro, strong proliferative responses were observed. The responding cells were shown to be a CD4 T ceil subset. It was also found that the CD4 T ceils secreted significant amounts of IFN-7 into the PBL culture supernatant. The production of IFN-7and IL-4 by PBL was measured semiquantitatively by reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…L. pneumophila infections are uncommon in patients with AIDS (122), although some reports suggested that the disease is more severe (261). The nature of the effector cells controlling L. pneumophila infection in humans is not clear, but in vitro studies show that Th1-type CD4 T cells respond to L. pneumophila by secreting IFN-␥ (193).…”
Section: Interactions With the Adaptive Immune Systemmentioning
confidence: 99%
“…L. pneumophila infections are uncommon in patients with AIDS (122), although some reports suggested that the disease is more severe (261). The nature of the effector cells controlling L. pneumophila infection in humans is not clear, but in vitro studies show that Th1-type CD4 T cells respond to L. pneumophila by secreting IFN-␥ (193).…”
Section: Interactions With the Adaptive Immune Systemmentioning
confidence: 99%
“…Kitsukawa et al found that mRNA for IFN-␥ but not IL-4 was produced by in vitro stimulation of human PBMCs with live or formalin-killed Legionella pneumophila (195). CD4 ϩ T-cell clones specific for L. pneumophila also expressed mRNA for IFN-␥ but not IL-4.…”
Section: Mycobacterial and Other Bacterial Diseasesmentioning
confidence: 99%